(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
The aim of the present work was to compare hepatitis C prevalence, genotypes, and risk factors between prisoners and non-prisoners in the city of Colatina, Espírito Santo, Brazil. This cross-sectional study involved approximately 1,600 residents and 730 prisoners, all of whom were living in Colatina. The percentage of individuals who tested positive for anti-HCV was 0.1% (2/1,600) in the non-prisoner group and 1.0% (7/730) in the prisoner group, confirming a higher risk of hepatitis C in the latter group. The percentage of subjects who progressed to HCV-RNA negative was 11.1% (1/9), confirming the high probability of evolution to chronicity. Genotype 1 was the most predominant genotype found. Factors associated with increased risk of hepatitis C were being male, being institutionalized, having an income of less than three minimum wages, having low educational attainment, and using injected drugs. Alcohol use, pain in the liver, migraine, and reported history of hepatitis were markedly associated with hepatitis C. The prison population tested positive for anti-HCV at a higher rate than the non-prison population.